Adenoviral infection in children admitted with severe acute respiratory infection at tertiary care hospital from North India: A case series - Rajarshi Bera; Pallavi Pallavi; Sonal Saxena; Shashi Chawla; Urmila Jhamb; Romit Saxena (Journal of Pediatric Critical Care)
There has been a recent surge in adenoviral infections with poor outcomes. This case series describes the clinical profile and outcome of 38 children admitted with adenovirus infection with severe acute respiratory illness (SARI). The majority (68.4%) were infants, 25 (65.7%) were immunocompetent, and 13 (34.2%) had an underlying comorbidity. Twenty-seven (71%) patients required mechanical ventilation and 5 (13.1%) were managed on a heated high-flow nasal cannula. Nine (23.6%) children developed acute respiratory distress syndrome and four (10.5%) cases developed postinfectious bronchiolitis obliterans (PIBO). The median duration of mechanical ventilation was 24 days interquartile range [11.5–34.5] days. Eleven (28.9%) children in the study population expired.